EARMYU: EXPANDING EDUCATION ACCESS AND EXCELLENCE TO HIGHLY MOBILE ONLINE LEARNERS - Stoskopf, Dian; Moorash, Amy (Online Learning, 2005)
eArmyU.com, 2004 winner of two Sloan-C awards—Excellence in Online Teaching and Programming and Effective Practice for Providing Anytime, Anywhere Online Access to Higher Education for a Highly Mobile Learner Population—is the Army’s state-of-the art online education portal. Through eArmyU, Soldiers can earn a postsecondary certificate or an associates, bachelor or master degree from a home institution while taking courses from multiple education partners. Credits transfer across institutions, enabling Soldiers quickly and conveniently to progress towards their educational goals. Soldiers can research degrees, apply for admission, submit assignments, access funding for courses, register for classes with the eArmyU education partners, and assess their progress from a single integrated Web site. Delivered by the Army Continuing Education System (ACES), eArmyU supports over 57,000 mobile Solider-students by partnering with 29 regionally accredited colleges and universities to deliver online asynchronous learning anytime anywhere.